ANALYSIS OF HOUSEHOLD CONSUMPTION AND WELFARE LEVEL OF WATER APPLE FARMERS IN TEBING GERINTING UTARA VILLAGE, SOUTH INDRALAYA SUB-DISTRICT, OGAN ILIR REGENCY - Eka Mulyana; Serly Novita Sari; Dini Damayanthy; M Huanza (Jurnal Ekonomi, 2023)
This study aims to analyze household consumption and the level of welfare of water apple farmer households in Tebing Gerinting Utara Village, South Indralaya District, Ogan Ilir Regency, South Sumatra. The research location was determined purposively with the consideration that the majority of the population in Tebing Gerinting Utara Village are water apple farmers. Sampling was taken randomly and only 30 samples were taken from a total of 613 water apple farmers. The analysis was carried out to answer the objective, namely using descriptive analysis and the Household Food Expenditure Share test and the Good Service Ratio (GSR) test to analyze the level of welfare of water apple farmer households. The research results obtained in this study are the household expenses of water apple farmers in Tebing Gerinting Utara Village is IDR 12,518,200/year which is divided into two categories, whicis food expenditure is IDR 5,401,200/year with the largest expenditure being the purchase of rice and non-food expenditure is Rp. 7,116,800/year with the largest expenditure is for purchase farmer's tobacco consumption. From the results of the PPP and GSR tests, it was found that water apple farmers in Tebing Gerinting Utara Village were able to buy and meet the main needs of their households and economically, farmer households were considered to be prosperous.